JURIDICAL ANALYSIS OF ARTICLE 167 PARAGRAPH (1) CONCERNING AGE AND WORKERS' RETIREMENT RIGHTS IN LAW NUMBER 13 OF 2003 - Huda, Nurul; Garavan, Thomas N. (EQUALEGUM International Law Journal, 2023)
Background. The National Development of the Republic of Indonesia is carried out in the context of the human development of Indonesia as a whole and the development of Indonesian society as a whole to create a society that is prosperous, just, prosperous, equitable both materially and spiritually based on Pancasila and the 1945 Constitution of the Republic of Indonesia. Doesn't set the retirement age limit, then the retirement age limit follows the statutory regulations that apply. This aimed to describe Law Number 13 of 2003 concerning Employment regulates the rights of workers/laborers such as pension rights. Research Method. This study uses primary and secondary data types for its descriptive empirical legal research. Findings. The Retirement Age Limit refers to the provisions in force at the Social Security Administering Body (BPJS of Employment. Because it is related to Old Age Security (JHT). Government Regulation Number 45 of 2015 Currently, the retirement age limit for workers/laborers according to the provisions is 56 years old. For this reason, every worker/laborer who experiences termination of employment will receive severance pay and the amount of value obtained by workers/laborers is under the conditions and causes at the time of the occurrence of work termination. Conclusion. Severance pay is calculated by the provisions of Law Number 13 of the Year 2003 and is also regulated in the Work Agreement, Company Regulations, and Collective Work Agreement.